(untitled) (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Chronic liver disease (CLD) is a significant global health problem marked by progressive hepatic injury and impaired liver function. One of the frequently overlooked yet clinically important complications of CLD is electrolyte imbalance. Electrolyte disturbances-particularly hyponatremia, hypokalemia, and hypocalcemia-are common in advanced liver disease. Objective: This study evaluate the patterns and prevalence of electrolyte disturbances in CLD patients, aiming to establish their association with disease severity. Methods: This observational cross-sectional study was conducted at Department of Hepatology, Comilla Medical College, Cumilla, Bangladesh, from January 2023 to December 2023. A total of 100 patients diagnosed with chronic liver disease (CLD) were included. Statistical analysis was performed using SPSS version 26.0. Result: In this study of 100 chronic liver disease patients, electrolyte imbalances were found to be highly prevalent, with hyponatremia in 58%, hypokalemia in 36%, and hypocalcemia in 41% of cases. These disturbances were more common in patients with advanced liver dysfunction (Child-Pugh Class B and C) and were significantly associated with complications such as ascites and hepatic encephalopathy. Conclusion: This study highlights the high prevalence of electrolyte imbalances-particularly hyponatremia, hypokalemia, and hypocalcemia-among patients with chronic liver disease. These abnormalities were significantly associated with the severity of liver dysfunction, as graded by the Child-Pugh classification, and were more frequent in patients with complications like ascites and hepatic encephalopathy. J Com Med Col Teachers’ Asso July 2025; 29(2):139-143